Interplay of Gravicentric, Egocentric, and Visual Cues About the Vertical in the Control of Arm Movement Direction. (March 2018) - Bock, Otmar; Bury, Nils
Our perception of the vertical corresponds to the weighted sum of gravicentric, egocentric, and visual cues. Here we evaluate the interplay of those cues not for the perceived but rather for the motor vertical. Participants were asked to flip an omnidirectional switch down while their egocentric vertical was dissociated from their visual–gravicentric vertical. Responses were directed mid-between the two verticals; specifically, the data suggest that the relative weight of congruent visual–gravicentric cues averages 0.62, and correspondingly, the relative weight of egocentric cues averages 0.38. We conclude that the interplay of visual–gravicentric cues with egocentric cues is similar for the motor and for the perceived vertical. Unexpectedly, we observed a consistent dependence of the motor vertical on hand position, possibly mediated by hand orientation or by spatial selective attention.